Research progress of nanomaterial drug delivery in tumor targeted therapy - Zhang, Peng; Ye, Guihua; Xie, Guofeng; Lv, Jie; Zeng, Xianhai; Jiang, Wei (Frontiers in Bioengineering and Biotechnology, 2023)
Cancer is one of the most lethal diseases in human society, and its incidence is gradually increasing. However, the current tumor treatment often meets the problem of poor efficacy and big side effects. The unique physical and chemical properties of nanomaterials can target the delivery of drugs to tumors, which can improve the therapeutic effect while reducing the damage of drugs to normal cells. This makes nanomaterials become a hot topic in the field of biomedicine. This review summarizes the recent progress of nanomaterials in tumor targeted therapy.